Polyimide and polyimide film

By using polyester materials derived from dialyne alcohol and diamine, and by controlling the FTIR spectral characteristics of specific ratio ranges, the problem of decreasing dielectric properties and CTE incompatibility of polyester materials after water absorption is solved, and stable dielectric properties and CTE compatibility is achieved.

JP2025043250AActive Publication Date: 2025-03-28CHANG CHUN PLASTICS CO LTD +1

Patent Information

Application Number
JP2024064321
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-15
Filing Date
2024-04-12
Publication Date
2025-03-28
Estimated Expiration
2044-04-12

AI Technical Summary

Technical Problem

When existing polyester materials are used as insulating materials for printed circuit boards in high speed and high frequency transmission, dielectric constant (Dk) and dielectric loss tangent (Df) are prone to decrease due to water absorption and their coefficient of thermal expansion (CTE) is incompatible with CTE of metal foils (such as copper foils), resulting in dielectric properties drop during water washing and drying, and possible peeling or popcorn problems.

Method used

Polyester materials derived from dialkynyl alcohol and diamine are used, which have characteristic peaks A, B and C in the FTIR spectrum, and by controlling the ratio range of b/a and c/b, the dielectric properties of the polyester material do not significantly decrease after water absorption and are compatible with the CTE of the metal foil.

Benefits of technology

The stability of the polyester material after water absorption is achieved and is compatible with the CTE of metal foil, avoiding the problem of dielectric properties drop and CTE mismatch during printed circuit board manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043250000001
    Figure 2025043250000001
  • Figure 2025043250000002
    Figure 2025043250000002
  • Figure 2025043250000003
    Figure 2025043250000003
Patent Text Reader

Abstract

To provide polyimide as an insulation material for preparing a printed circuit board.SOLUTION: Polyimide includes one or a plurality of repeating units derived from dianhydride, and one or a plurality of repeating units derived from diamine. Infrared absorption spectrum of the polyimide obtained through Fourier transform infrared spectroscopy (FTIR) using attenuated total reflection (ATR) has a characteristic peak A of 1,753 cm-1 to 1,803 cm-1, a characteristic peak B of 1,635 cm-1 to 1,752 cm-1, and a characteristic peak C of 1,160 cm-1 to 1,170 cm-1, the characteristic peak A has a characteristic peak area a, the characteristic peak B has a characteristic peak area b, the characteristic peak C has a characteristic peak area c, b / a is 25.00 or less, and c / b is 0.3000 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to polyimides, and more particularly to polyimides having specific Fourier transform infrared spectral characteristics. Further, the present application relates to polyimide films. [Background technology]

[0002] For high speed and high frequency transmission, the insulating material used in the manufacture of printed circuit boards requires low dielectric constant (Dk) and low dissipation factor (Df). Typically, these dielectric properties can be significantly degraded by moisture absorption. However, considering the processes such as black oxide treatment, water rinsing, and drying during the preparation of printed circuit boards, it is important that the insulating material of the printed circuit board maintains good dielectric properties even after the water rinsing and drying process. In addition, to prevent problems such as delamination or popcorn problems during the manufacture of printed circuit boards, the insulating material of the printed circuit board should match the coefficient of thermal expansion (CTE) of the metal foil (e.g., copper foil).

[0003] Polyimides are well-known insulating materials for preparing printed circuit boards. However, current polyimides have several problems, such as poor dielectric properties, high water absorption, CTE mismatch with metal foils, and significant degradation of dielectric properties after water absorption. Therefore, further improvements are needed for existing polyimides. Summary of the Invention

[0004] In view of the above, the present application provides a polyimide derived from a dianhydride and a diamine. The polyimide of the present application exhibits excellent dielectric properties, low water absorption, and a CTE that matches that of metal foil. Furthermore, the dielectric properties of the polyimide of the present application do not deteriorate significantly after absorbing water, making it particularly suitable as an insulating material for printed circuit boards.

[0005] The object of the present application is to provide a polyimide comprising one or more repeat units derived from a dianhydride and one or more repeat units derived from a diamine, the infrared absorption spectrum of which, obtained by Fourier transform infrared spectroscopy (FTIR) using attenuated total reflectance (ATR), has a peak at 1753 cm -1 From 1803cm -1 Characteristic peak A, 1635 cm -1 From 1752cm -1 The characteristic peaks B and 1160 cm -1 From 1170cm -1 wherein characteristic peak A has a characteristic peak area a, characteristic peak B has a characteristic peak area b, and characteristic peak C has a characteristic peak area c, wherein the ratio of b to a, i.e., b / a, is 25.00 or less, and the ratio of c to b, i.e., c / b, is 0.3000 or more.

[0006] In some embodiments of the present application, 10.00≦b / a≦25.00.

[0007] In some embodiments of the present application, 10.00≦b / a≦18.50.

[0008] In some embodiments of the present application, 0.32≦c / b≦0.54.

[0009] In some embodiments of the present application, 0.34≦c / b≦0.52.

[0010] In some embodiments of the present application, the FTIR uses ZnSe as a crystal for attenuated total reflection and has a scan range of 650 cm -1 From 4000cm -1 , and the measurement is performed with 8 scans.

[0011] In some embodiments of the present application, the one or more repeat units derived from a diamine include a repeat unit derived from an aliphatic diamine.

[0012] In some embodiments of the present application, the one or more repeat units derived from a diamine include a repeat unit derived from an aliphatic diamine and a repeat unit derived from an aromatic diamine.

[0013] In some embodiments of the present application, the one or more repeat units derived from a dianhydride include a repeat unit derived from an aromatic dianhydride.

[0014] In some embodiments of the present application, the backbone of the polyimide includes one or more ester groups.

[0015] In some embodiments of the present application, the ratio of the number of ester functional groups to imide functional groups, based on the total number of all functional groups of the polyimide, is 0.8 or greater.

[0016] Another object of the present application is to provide a polyimide film prepared from the aforementioned polyimide.

[0017] In order to make the above objectives, technical features and advantages of the present application more apparent, the present application is described in detail below with reference to several embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS In the following, some embodiments of the present application will be described in detail. However, the present application may be embodied in various forms and should not be construed as being limited to the embodiments set forth herein.

[0019] Unless otherwise specified, the terms "a", "the", and the like used in the specification and claims are intended to include both the singular and the plural.

[0020] The polyimides of the present application exhibit excellent dielectric properties, low water absorption, a CTE that matches (i.e., is similar to) the CTE of the metal foil, and maintain good dielectric properties even after absorbing water. Further details regarding the polyimides of the present application and their applications are provided below.

[0021] 1. Polyimide

[0022] 1.1 Characteristics of polyimide

[0023] The polyimides of the present application have a specific infrared spectrum. The infrared spectrum is obtained by Fourier transform infrared spectroscopy (FTIR) using attenuated total reflectance (ATR). The infrared spectrum of the polyimides of the present application has a peak at 1753 cm -1 From 1803cm -1 Characteristic peak A, 1635 cm -1 From 1752cm -1 The characteristic peaks B and 1160 cm -1 From 1170cm -1 characteristic peak A has a characteristic peak area a, characteristic peak B has a characteristic peak area b, and characteristic peak C has a characteristic peak area c.

[0024] In the infrared spectrum of the polyimides of the present application, the ratio of b to a, i.e., b / a, is 25.00 or less. For example, b / a is 25.00, 24.75, 24.50, 24.25, 24.00, 23.75, 23.50, 23.25, 23.00, 22.75, 22.50, 22.25, 22.00, 21.75, 21.50, 21.25, 21.00, 20.75, 20.50, 20.25, 20.00, 19.75, 19.50, 19.25, 19. 00, 18.75, 18.50, 18.40, 18.25, 18.00, 17.75, 17.50, 17.25, 17.00, 16.75, 16.50, 16.25, 16.00, 15.75, 15.50, 15.25, 15.00, 14.75, 14.50, 14.25, 14.00, 13.75, 13.50, 13.25, 13.00, 12.7 5, 12.50, 12.25, 12.00, 11.75, 11.50, 11.25, 11.00, 10.75, 10.50, 10.25, 10.05, 10.00, 9.75, 9.50, 9.25, 9.00, 8.75, 8.50, 8.25, 8.00, 7.75, 7.50, 7.25, 7.00, 6.75, 6.50, 6.25, 6.00, 5. b / a may be 75, 5.50, 5.25, 5.00, 4.75, 4.50, 4.25, 4.00, 3.75, 3.50, 3.25, 3.00, 2.75, 2.50, 2.25, 2.00, 1.75, 1.50, 1.25, 1.00, 0.75, 0.50, or 0.25, or within a range between any two values ​​listed herein. In some embodiments of the present application, 10.00≦b / a≦25.00, specifically 10.00≦b / a≦18.50, and more specifically 10.05≦b / a≦18.40. If the b / a value of the polyimide is outside the specified range, the CTE of the polyimide will not match the CTE of the copper foil, and the dielectric properties of the polyimide after water absorption will be significantly reduced.

[0025] In the infrared spectrum of the polyimide of the present application, the ratio of c to b, i.e., c / b, is 0.3000 or more. For example, c / b is 0.3000, 0.3100, 0.3200, 0.3300, 0.3350, 0.3400, 0.3450, 0.3500, 0.3600, 0.3700, 0.3800, 0.3900, 0.4000, 0.4100, 0.4200, 0.4300, 0.4400, 0.4500, 0.4600 ,0.4700,0.4800,0.4900,0.5000,0.5100,0.5200,0.5300,0.5400,0.5500,0.5600,0.5700,0.5800,0.5900,0.6000,0.6100,0.6200,0.6300,0.6400,0.6500,0.6600, 0.6700, 0.6800, 0.6900, 0.7000, 0.7100, 0.7200, 0.7300, 0.7400, 0.7500, 0.7600, 0.7700, 0.7800, 0.7900, 0.8000, 0.8100, 0.8200, 0.8300, 0.8400, 0.8500, 0.8600, 0 The c / b value may be 0.8700, 0.8800, 0.8900, 0.9000, 0.9100, 0.9200, 0.9300, 0.9400, 0.9500, 0.9600, 0.9700, 0.9800, 0.9900, or 1.0000, or within a range between any two values ​​listed herein. In some embodiments of the present application, 0.32≦c / b≦0.54, specifically 0.34≦c / b≦0.52, more specifically 0.345≦c / b≦0.52. If the c / b value of the polyimide is out of the specified range, the polyimide cannot have a CTE similar to that of the copper foil, and the dielectric properties of the polyimide after water absorption will be significantly reduced.

[0026] The FTIR measurement is performed under the following conditions: ZnSe is used as a crystal for attenuated total reflection, and 650 cm -1 From 4000cm -1 The scanning range is 8, the number of scans is 1 cm. -1 The FTIR measurement was performed with a resolution of 100 kHz. The ATR jig (model: MIRacle) manufactured by PIKE Technologies was used. TMThe infrared spectrometer used is a Perkin Elmer FTIR spectrometer spectrum two, using a single reflection ATR. Data analysis is performed using Perkin Elmer 10.5.3.738 software. The software identifies the start, peak, and end of the characteristic peak (i.e., selects the point where the first derivative is zero), and then calculates the characteristic peak area encompassing the range from the start to the peak and end through software integration.

[0027] 1.2. Polyimide structure and preparation

[0028] In general, polyimides can be synthesized by two major methods: two-step condensation and one-step condensation. In the two-step condensation method, a condensation polymerization reaction between a dianhydride and a diamine produces a poly(amic acid) (PPA), which is then heated, dehydrated, and cyclized to form a polyimide. In the one-step condensation method, a dianhydride and a diisocyanate are reacted at high temperature to directly produce a polyimide.

[0029] The method for preparing the polyimide of the present application is not particularly limited. In some embodiments of the present application, the polyimide is synthesized using a two-step condensation method by polymerizing a dianhydride and a diamine, resulting in a polyimide containing repeating units derived from the dianhydride and the diamine. First, the diamine is introduced into a flask under a nitrogen atmosphere and dissolved in a solvent. Then, the dianhydride is added to form an intermediate solution, which is stirred at room temperature for 12 hours to produce a poly(amic acid) solution. Then, the solution is subjected to a high-temperature heating cyclization reaction to obtain a polyimide. The preparation of the polyimide of the present application is preferably carried out under the following conditions: (1) based on the total amount of diamines, the amount of long-chain aliphatic diamine is preferably 20 mol% or less; (2) based on the total number of all functional groups of the polyimide, the ratio of the number of ester functional groups to the number of imide functional groups is 0.8 to 2.0 (0.8 to 2.0).

[0030] The type of dianhydride used in forming the polyimide of the present application is not particularly limited. Examples of dianhydrides include, but are not limited to, 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), pyromellitic dianhydride (PMDA), 5-isobenzofuran carboxylic acid, 1,3-dihydro-1,3-dioxo-,1,4-phenylene ester (TAHQ), 4,4'-bisphenol A dianhydride (BPADA), 4,4'-oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and hydroquinone diphthalic anhydride (HQDA). The above dianhydrides can be used alone or in combination of two or more. In some embodiments of the present application, the one or more repeat units derived from a diamine include a repeat unit derived from an aromatic diamine, which can be selected from the group consisting of a-BPDA, s-BPDA, TAHQ, BTDA, ODPA, and combinations thereof.

[0031] The type of diamine used in forming the polyimide of the present application is not particularly limited. The diamine may be an aliphatic diamine or an aromatic diamine. Examples of aliphatic diamines include, but are not limited to, 1,2-ethylenediamine, 1,2-propylenediamine, 1,3-diaminopropane, 1,5-diaminopentane, 1,4-bis(aminomethyl)cyclohexane, 4,4'-methylenebis(2-methylcyclohexylamine), octamethylenediamine (OMDA), isophoronediamine (IPDA), 4,4'-diaminodicyclohexylmethane, hexamethylenediamine (HMDA), octamethylenediamine (OMDA), 3,3'-dimethyl-4,4'-diamino-dicyclohexylmethane, C36 dimer diamine (C36 DDA), C38 dimer diamine, and C40 dimer diamine. Examples of the dimer diamines include those derived from oleic acid, linoleic acid, linolenic acid, palmitoleic acid, or elaidic acid. Products such as Priamine 104 or Priamine 1075 available from Croda are examples of such dimer diamines. The aliphatic diamines can be used alone or in combination of two or more.Examples of aromatic diamines include, for example, bis(4-aminophenyl)terephthalate (BPTP), 1,4-bis(4-aminobenzoyloxy)benzene (ABHQ), 4-aminophenyl-4-aminobenzoate (APAB), 4,4'-oxydianiline (ODA), p-phenylenediamine (PPD), bis(4-aminophenyl)deca-hydronaphthalene-2,6-dicarboxylate (ET-BDM), 2,7-bis(4-aminophenoxy)naphthalene (ET-2,7-Na), N,N'-(4,4'-(9H-fluorene-9,9-diyl)bis(4,1-phenylene))bis(4-aminobenzamide) (FDA-ADA), 4,4'-( Examples of the aromatic diamine include, but are not limited to, hexafluoroisopropylidene)dianiline (6FPDA), 4,4'-(hexafluoroisopropylidene)bis(p-phenyleneoxy)dianiline (BAPHF), bis[4-(3-aminophenoxy)phenyl]sulfone (BAPS), 4,4'-diaminobenzanilide (DABA), N1,N4-bis(4-aminophenyl)terephthalamide (BPTPA), 4,4'-(4,4'-oxybis(4,1-phenylene)bis(oxy))bis(3-(trifluoromethyl)-aniline) (p-6FAPE), and bis(4-aminophenyl)-cyclohexane-1,4-dicarboxylate (ES-C). The aromatic diamines may be used alone or in combination. In one embodiment of the present application, the polyimide comprises one or more repeating units derived from an aliphatic diamine. In another embodiment of the present application, the polyimide comprises one or more repeat units derived from an aliphatic diamine and one or more repeat units derived from an aromatic diamine. The aliphatic diamine, preferably a long chain aliphatic diamine, along with the aromatic diamine, can be selected from the group consisting of PPD, ODA, C36 DDA, ABHQ, BPTP, and combinations thereof.

[0032] Examples of solvents for dissolving dianhydrides and diamines include, but are not limited to, N,N-dimethylacetamide (DMAc), N,N-dimethylformamide, N-methylpyrrolidone (NMP), dimethylsulfoxide (DMSO), acetonitrile, hexamethylphosphoric acid triamide (HMPA), and 1,3-dimethyl-2-imidazolidinone (DMI). The above solvents can be used alone or in combination of two or more.

[0033] In some embodiments of the present application, the backbone of the polyimide contains one or more ester groups (-C(=O)-O-). The polyimide can be formed by polymerizing an ester group-containing dianhydride and a diamine, a dianhydride and an ester group-containing diamine, or an ester group-containing dianhydride and an ester group-containing diamine. Examples of ester group-containing dianhydrides include, but are not limited to, TAHQ. Examples of ester group-containing diamines include, but are not limited to, ABHQ, APAB, and BPTP.

[0034] In a preferred embodiment of the present application, the ratio of the number of ester functional groups to the number of imide functional groups, based on the total number of all functional groups in the polyimide, is 0.8 or more, preferably 0.8 to 2.0. For example, the ratio of the number of ester functional groups to the number of imide functional groups, based on the total number of all functional groups in the polyimide, can be 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0, or a range between any two of the values ​​listed herein. If the ratio of the number of ester functional groups to the number of imide functional groups in the polyimide is 0.8 or more, the dielectric properties of the polyimide and the dielectric properties of the polyimide after absorbing water can be further improved.

[0035] 2. Polyimide film

[0036] The polyimide of the present application is suitable for producing film products. Therefore, the present application also provides a polyimide film. The method for producing the polyimide film of the present application is not particularly limited. The polyimide film can be produced by applying the polyimide by a conventional coating method prevalent in the art. Alternatively, the polyimide film can be produced by coating a poly(amic acid) solution using a conventional coating method prevalent in the art to form a poly(amic acid) film, followed by heating to introduce a thermal cyclization reaction in the poly(amic acid) film. Examples of conventional coating methods include, but are not limited to, roller coating, blade coating, comma coating, die coating, slot die coating, wire bar coating, and spray coating.

[0037] In some embodiments of the present application, the polyimide film is prepared by the following procedure. First, the poly(amic acid) solution is filtered to remove dust and impurities. Then, the filtered poly(amic acid) solution is coated onto a cleaned glass substrate using a blade mold. The coated glass substrate is then subjected to a vacuum treatment for 4 to 8 hours to gradually remove the solvent. Next, the glass substrate is placed in a high-temperature and high-pressure oven to induce the thermal cyclization reaction of the poly(amic acid) to form polyimide and obtain a polyimide film. The obtained polyimide film is slowly cooled and subjected to a multi-step heat treatment at 100°C to 500°C to stabilize the polyimide film. Finally, the polyimide film is slowly cooled to room temperature to prevent the film from cracking.

[0038] The polyimide film of the present application exhibits excellent dielectric properties, low water absorption, and a CTE that matches that of metal foil. In addition, the dielectric properties of the polyimide film of the present application do not decrease significantly after water absorption. As a result, the polyimide film of the present application is particularly suitable as an insulating material for printed circuit boards. The thickness of the polyimide film of the present application is preferably 10 μm to 50 μm. For example, the thickness of the polyimide film of the present application can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, 40 μm, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm, 46 μm, 47 μm, 48 μm, 49 μm, or 50 μm, and can be within a range between any two of the values ​​listed herein. EXAMPLES

[0039] 3. Working Example

[0040] Test Method

[0041] The present application is further illustrated by the following specific examples, test equipment and methods:

[0042] [FTIR analysis]

[0043] A polyimide film with a length of 5 cm, a width of 5 cm, and a thickness of at least 10 μm is prepared as a sample. TM The samples are subjected to FTIR analysis using an infrared spectrometer (Model: FTIR spectrometer spectrum two) equipped with a single reflection ATR and Perkin Elmer 10.5.3.738 software. The analysis is performed under the following conditions: ZnSe is used as a crystal for attenuated total reflection, 650 cm -1 From 4000cm -1The scanning range is 8, the number of scans is 1 cm. -1 The resolution is

[0044] In the resulting infrared absorption spectrum of the polyimide, the software is used to identify the points where the first derivative reaches zero and designate these points as the start, maximum, and end of the characteristic peaks. The software then calculates the characteristic peak areas encompassing the ranges from the start to the maximum and end via software integration.

[0045] [Measurement of dielectric properties]

[0046] A sample of polyimide film with a length of 8 cm, a width of 8 cm, and a thickness of at least 10 μm is vacuum dried at 100° C. for 24 hours. The dielectric constant (Dk) and dissipation factor (Df) of the dried sample are then measured to obtain the dielectric properties before water absorption. The measurements are performed using a vector network analyzer (model: R&S® ZVB, available from Rohde & Schwarz) at an analysis frequency of 10 GHz.

[0047] Also, a sample of polyimide film with a length of 8 cm, a width of 8 cm, and a thickness of at least 10 μm is immersed in water for 24 hours, then wiped dry. The immersed sample goes through the aforementioned Dk and Df measurement steps to obtain the dielectric properties after water absorption.

[0048] [Water absorption test]

[0049] The water absorption of polyimide film is measured in accordance with IPC-TM-650 2.6.2.1 and calculated using the following formula: where W 1 represents the weight of the polyimide film measured after drying in an oven at 105 °C, and W 2 represents the weight of the polyimide film after immersion in water at 23° C. for 24 hours and then removing the water droplets. The polyimide film sample is 2 inches long, 2 inches wide, and 25 μm thick.

[0050]

number

[0051] [Measurement of coefficient of thermal expansion (CTE)]

[0052] The CTE of the polyimide film is measured using a thermomechanical analyzer (model: TMA Q400, available from TA Instruments). The measurement conditions are as follows: the polyimide film sample to be measured is 10 mm long, 5 mm wide, and 20 μm thick, the test is performed under a dry nitrogen atmosphere, and the measurement temperature range of the CTE is 50° C. to 300° C. The unit of CTE is ppm / K.

[0053] 3.2. Preparation of poly(amic acid) solution

[0054] [Example 1]

[0055] First, 7.11 g (0.0204 mol) of ABHQ (available from ShiFeng Technology Co., Ltd.) and 1.21 g (0.0023 mol) of C35 DDA (model: Priamine 1074, available from Croda Company Co., Ltd.) were placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 15 wt %. Then, the intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to the intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 6.68 g (0.0227 mol) of s-BPDA (available from UBE Company Co., Ltd.) was added to the intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Then, 0.05 mmol of acetic anhydride was added as a cyclization agent, and the resulting solution was stirred for 30 minutes to ensure that acetic anhydride was completely dissolved, obtaining a poly(amic acid) solution of Example 1.

[0056] [Example 2]

[0057] First, 6.15 g (0.0177 mol) of ABHQ and 2.36 g (0.0044 mol) of C36 DDA were placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 15 wt%. Then, the intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to the intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 6.49 g (0.0221 mol) of s-BPDA was added to the intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Then, 0.05 mmol of acetic anhydride was added as a cyclizing agent, and the resulting solution was stirred for 30 minutes to confirm that acetic anhydride was completely dissolved, and a poly(amic acid) solution of Example 2 was obtained.

[0058] [Example 3]

[0059] First, 6.15 g (0.0177 mol) of BPTP (available from ShiFeng Technology Co., Ltd.) and 2.36 g (0.0044 mol) of C36 DDA were placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 15 wt%. Then, the intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to the intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 6.49 g (0.0221 mol) of s-BPDA was added to the intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Then, 0.05 mmol of acetic anhydride was added as a cyclization agent, and the resulting solution was stirred for 30 minutes to ensure that acetic anhydride was completely dissolved, obtaining a poly(amic acid) solution of Example 3.

[0060] [Example 4]

[0061] First, 1.91 g (0.0177 mol) of PPD (available from ShiFeng Technology Co., Ltd.) and 1.52 g (0.0076 mol) of ODA (available from Li Yung Far Technology Co., Ltd.) were placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 10 wt %. Then, the intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to the intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 11.57 g (0.0252 mol) of TAHQ (available from ShiFeng Technology Co., Ltd.) was added to the intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Then, 0.05 mmol of acetic anhydride was added as a cyclization agent, and the resulting solution was stirred for 30 minutes to ensure that acetic anhydride was completely dissolved, obtaining a poly(amic acid) solution of Example 4.

[0062] [Example 5]

[0063] First, 5.8 g (0.0167 mol) of ABHQ and 0.99 g (0.0019 mol) of C36 DDA were placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 15 wt%. Then, the intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to the intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 7.63 g (0.0167 mol) of TAHQ and 0.57 g (0.0019 mol) of ODPA (available from Li Yung Far Technology Co., Ltd.) were added to the intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Then, 0.05 mmol of acetic anhydride was added as a cyclization agent, and the resulting solution was stirred for 30 minutes to ensure that acetic anhydride was completely dissolved, obtaining a poly(amic acid) solution of Example 5.

[0064] [Comparative Example 1]

[0065] First, 8.13 g (0.0233 mol) of BPTP was placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 15 wt%. Then, this intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to this intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 6.87 g (0.0233 mol) of s-BPDA was added to this intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Next, 0.05 mmol of acetic anhydride was added as a cyclizing agent, and the resulting solution was stirred for 30 minutes to confirm that acetic anhydride was completely dissolved, and a poly(amic acid) solution of Comparative Example 1 was obtained.

[0066] [Comparative Example 2]

[0067] First, 8.13 g (0.0233 mol) of ABHQ was placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 15 wt%. Then, this intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to this intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 6.87 g (0.0233 mol) of s-BPDA was added to this intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Next, 0.05 mmol of acetic anhydride was added as a cyclizing agent, and the resulting solution was stirred for 30 minutes to confirm that acetic anhydride was completely dissolved, and a poly(amic acid) solution of Comparative Example 2 was obtained.

[0068] [Comparative Example 3]

[0069] First, 6.48 g (0.0186 mol) of BPTP was placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 15 wt%. Then, this intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to this intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 8.52 g (0.0186 mol) of TAHQ was added to this intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Next, 0.05 mmol of acetic anhydride was added as a cyclization agent, and the resulting solution was stirred for 30 minutes to confirm that acetic anhydride was completely dissolved, and a poly(amic acid) solution of Comparative Example 3 was obtained.

[0070] [Comparative Example 4]

[0071] First, 6.48 g (0.0186 mol) of ABHQ was placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 15 wt%. Then, this intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to this intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 8.52 g (0.0186 mol) of TAHQ was added to the intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Next, 0.05 mmol of acetic anhydride was added as a cyclizing agent, and the resulting solution was stirred for 30 minutes to confirm that acetic anhydride was completely dissolved, and a poly(amic acid) solution of Comparative Example 4 was obtained.

[0072] [Comparative Example 5]

[0073] First, 6.07 g (0.0303 mol) of ODA was placed in a flask. Then, 85 mL of anhydrous DMAc was added, and the mixture was stirred at 80° C. to dissolve, preparing an intermediate solution with a concentration of 10 wt%. Then, this intermediate solution was placed in an ice bath. 5.5 mmol of glacial acetic acid was slowly added to this intermediate solution, and the intermediate solution was stirred for 10 minutes. Then, 8.93 g (0.0303 mol) of s-BPDA was added to this intermediate solution, and the intermediate solution was stirred at room temperature for 15 hours. Next, 0.05 mmol of acetic anhydride was added as a cyclizing agent, and the resulting solution was stirred for 30 minutes to confirm that acetic anhydride was completely dissolved, and a poly(amic acid) solution of Comparative Example 5 was obtained.

[0074] 3.3. Preparation of polyimide film

[0075] Polyimide films were produced using the poly(amic acid) solutions of Examples 1 to 5 and Comparative Examples 1 to 5, respectively. First, the poly(amic acid) solutions were filtered using a 0.45 μm filter head to remove dust and impurities. Next, the filtered poly(amic acid) solution was applied onto a cleaned glass substrate (length 20 cm, width 20 cm, thickness 0.5 cm) using a 600 μm blade mold. Next, the glass substrate coated with the poly(amic acid) solution was placed in a vacuum environment for 6 hours to gradually remove the solvent. Thereafter, the glass substrate coated with the poly(amic acid) solution was heat-treated at 100° C., 200° C., 300° C., and 350° C. for 1 hour, respectively, to thermally cyclize the poly(amic acid) to form a polyimide film, and the properties of the polyimide film were stabilized. Finally, in order to prevent cracking of the film, the polyimide film was slowly cooled to room temperature to produce the polyimide films of Examples 1 to 5 and Comparative Examples 1 to 5.

[0076] 3.4. FTIR, dielectric properties and CTE analysis of polyimide films

[0077] The polyimide films of Examples 1 to 5 and Comparative Examples 1 to 5 were subjected to the above-mentioned test methods for various properties including FTIR analysis, Dk, Df and CTE. The results are shown in Tables 1 to 4.

[0078] Table 1: FTIR analysis of the polyimide films of the examples

[0079] [Table 1]

[0080] Table 2: FTIR analysis of comparative polyimide films

[0081] [Table 2]

[0082] Table 3: Properties of the polyimide films of the examples

[0083] [Table 3]

[0084] Table 4: Properties of polyimide films of comparative examples [Table 4]

[0085] Regarding the CTE of the metal foil (e.g., copper foil) and the CTE of the adhesive resin, it is preferable that the CTE value of the polyimide film used in the manufacture of the printed circuit board is matched with the CTE value of the metal foil. Generally, the CTE value of the polyimide film is in the range of 10 ppm / °C to 40 ppm / °C, preferably in the range of 20 ppm / °C to 40 ppm / °C, to prevent peeling or popcorn problems during the printed circuit board manufacturing process. As shown in Table 3, the polyimide film of the present application not only has excellent Df and Dk, but also has a CTE similar to that of the metal foil. In contrast, as shown in Table 4, the polyimide film not according to the present application cannot simultaneously achieve excellent Df and Dk, and a CTE that matches the metal foil. In particular, Comparative Examples 1 and 2 show that when the c / b value of the polyimide is out of the specified range of the present application, the resulting polyimide film does not have excellent dielectric properties and the CTE does not match the metal foil, even though the b / a value of the polyimide is within the specified range of the present application. Comparative Example 4 shows that when the b / a value of the polyimide is outside the range specified in this application, the CTE of the resulting polyimide film does not match the CTE of the metal foil even if the c / b value meets the range specified in this application. Comparative Examples 3 and 5 show that when both the b / a value and the c / b value of the polyimide are outside the range specified in this application, the CTE of the resulting polyimide film does not match the CTE of the metal foil. In particular, the CTE value of the polyimide film of Comparative Example 3 is significantly lower than that of the metal foil.

[0086] 3.5. Water absorption rate of polyimide film and dielectric properties after water absorption

[0087] According to the above-mentioned test method, the polyimide films of Examples 1 to 3 and 5 and Comparative Examples 1, 2, 4 and 5 were further subjected to a water absorption test and the dielectric properties after water absorption were measured. The results are shown in Tables 5 and 6.

[0088] Table 5: Dielectric properties and water absorption rate of the polyimide films of the examples after water absorption

[0089] [Table 5]

[0090] Table 6: Dielectric properties and water absorption rate of the polyimide film of the comparative example after water absorption

[0091] [Table 6]

[0092] As shown in Table 5, the polyimide film of the present application has a low water absorption rate and good Df and Dk even after water absorption and drying. Therefore, the polyimide film of the present application can be suitably used as an insulating material for printed circuit boards. In contrast, as shown in Table 6, polyimide films other than the polyimide film of the present application cannot maintain good values ​​of Df and Dk after water absorption and drying, and are unsuitable for use as an insulating material for printed circuit boards.

[0093] The above examples are used to explain the principle and effectiveness of the present application and to demonstrate the features of the present invention, but are not used to limit the scope of the present application. Those skilled in the art can proceed with various modifications and substitutions based on the disclosure and suggestions of the present invention described. Therefore, the protection scope of the present application is as defined in the appended claims.

Claims

1. A polyimide comprising one or more repeat units derived from a dianhydride and one or more repeat units derived from a diamine, wherein the infrared absorption spectrum of the polyimide obtained by Fourier transform infrared spectroscopy (FTIR) using attenuated total reflectance (ATR) has a peak at 1753 cm -1 From 1803 cm -1 Characteristic peak A at 1635 cm -1 From 1752 cm -1 The characteristic peak B at 1160 cm -1 From 1170 cm -1 wherein the characteristic peak A has a characteristic peak area a, the characteristic peak B has a characteristic peak area b, the characteristic peak C has a characteristic peak area c, and b / a is 25.00 or less and c / b is 0.3000 or more.

2. 2. The polyimide according to claim 1, wherein 10.00≦b / a≦25.

00.

3. 3. The polyimide according to claim 2, wherein 10.00≦b / a≦18.

50.

4. 2. The polyimide according to claim 1, wherein 0.32≦c / b≦0.

54.

5. 5. The polyimide according to claim 4, wherein 0.34≦c / b≦0.

52.

6. The FTIR uses ZnSe as a crystal for attenuated total reflection and has a scanning range of 650 cm -1 From 4000cm -1 6. The polyimide according to claim 1 , wherein the thickness is 100 nm and the number of scans is 8.

7. 6. The polyimide of claim 1, wherein the one or more repeat units derived from a diamine include a repeat unit derived from an aliphatic diamine.

8. 8. The polyimide of claim 7, wherein the one or more repeat units derived from a diamine further comprises a repeat unit derived from an aromatic diamine.

9. 6. The polyimide of claim 1, wherein the one or more repeat units derived from a dianhydride comprise a repeat unit derived from an aromatic dianhydride.

10. 6. The polyimide of claim 1, wherein the backbone of the polyimide contains one or more ester groups.

11. A polyimide film prepared from the polyimide of any one of claims 1 to 5.

Citation Information

Patent Citations

  • New ester group-containing tetracarboxylic acid dianhydride, new polyester imide precursor to be derived therefrom, and polyester imide

    JP2014001394A

  • Polyimide and a film using the same

    JP2017514972A

  • Multilayer polyimide film

    JP2021074894A

  • Ester group-containing tetracarboxylic acid dianhydride, polyester polyimide precursor, polyesterimide, and methods for producing same

    WO2010093021A1

Cited By

  • Polyamic acid polycondensation stage dynamics monitoring method based on in-situ infrared detection

    CN121856200A

  • Polyamide acid polycondensation stage kinetics monitoring method based on in-situ infrared detection

    CN121856200B

  • Solid pharmaceutical compositions

    CN122768245A